Barriers To Village Asset Management And Regional Government Policies In Overcoming Them - Yusuf Eko Nahuddin (International Journal of Sociology and Law, 2024)
This research aims to determine the obstacles in managing village assets as well as regional government policies in overcoming obstacles to managing village assets. This research method uses empirical legal research with a sociological juridical approach. As for the research results that obstacles in managing village assets include village assets, especially village treasury land, which are mostly controlled by third parties, unequal potential for village assets, inharmonious conditions of village government, difficulty in making decisions in determining the fair value of village assets, not actually including the results of village asset management. into the APBDes. As for the government's policies in overcoming these obstacles, the DPRD and the regional government periodically carry out synergistic activities through Focus Group Discussions (FGD) to unravel problems in managing village assets, the government together with the DPRD always receive complaints and mediate to find solutions related to obstacles in managing village assets, The DPRD encourages regional governments through sub-districts to provide assistance in submitting minutes of the handover of the position of village head in relation to the inventory of village assets, and the Government together with the DPRD carry out studies to amend or adjust Regional Regulations or Regent Regulations regarding village asset management according to input from the village government with prior implementation. comprehensive study.